Stopped in their tracks Hikers barred from entering Ayer Hitam Forest Reserve - The Star, Tan Karr Wei (2012)
HIKERS. at the Ayer Hitam Forest Reserve had a rude surprise when they were denied entry by security guards stationed at the entrance last Saturday.